TRADISI BELE KAMPUNG PADA MASYARAKAT DI DUSUN TANJUNG DESA SEKODI KECAMATAN BENGKALIS KABUPATEN BENGKALIS - ", Sumarni; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The research was conducted in Tanjung hamlet, Sekodi village. The purpose of this study was to determine the process of implementing the tradition of Bele Kampung in Tanjung hamlet Sekodi Village. The topic of this research is the implementation process and the meaning of Bele Kampung tradition in the community of Tanjung hamlet Sekodi village. by purposive sampling and determine the number of subjects as many as 10 people. The author uses descriptive qualitative methods and data instruments are observation, interviews and documentation. Research found that the village tradition was held once a year, and carried out at the home of the implementing dukun. This tradition was carried out after getting the results of the deliberations , the village tradition was carried out for three consecutive days. On the first day of delivering the tools to Tanjung, and recited a congratulatory prayer there, then returned with water. The water was used for the bathing process on the third day. On the second day of carrying out the swinging process, The people were given words of advice and then tipped with fresh flour. After they finished swinging and patring fresh flour, the pebuang tools were then delivered to Tumu, to Nipah and to Baran, and to throw the ancak used for swinging. On the third day of the Tanjung Hamlet community carrying out the process of bathing, namely bathing with water mixed from three sacred places, namely sacred Tanjung, Nipah and Tumu. The people of Tanjung Hamlet explain that the tradition of bele kampung aims to keep the community from dangers, and facilitate the search for sustenance. the village was also guarded and carried out, so that none of the people of Tanjung Hamlet dared to violate abstinence. In addition to the goal of avoiding danger, the tradition of village dwelling was also carried out to maintain the traditions of their ancestral heritage.Keywords: Tradition, Culture, Bele Kampung